Back Cover: Vibrational Dephasing in Ionic Liquids as a Signature of Hydrogen Bonding (ChemPhysChem 12/2015). Issue 12 (24th August 2015) - Chatzipapadopoulos, Susana; Zentel, Tobias; Ludwig, Ralf; Lütgens, Matthias; Lochbrunner, Stefan; Kühn, Oliver
<x xml:space="preserve">Abstract</x> Hydrogen bonding governs the vibrational dephasing in ionic liquids. Time‐resolved coherent anti‐Stokes Raman scattering (CARS) and theoretical studies show that this process takes place on the fs‐to‐ps timescale. More information can be found in the Full Paper by R. Ludwig, S. Lochbrunner, O. Kühn et al. on p. 2519.